2022
DOI: 10.1109/jsen.2022.3202101
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Infill Pattern and Density on the Response of 3-D-Printed Sensors Based on FBG Technology

Abstract: Fiber Bragg gratings (FBGs) are known for their uses in applications ranging from civil engineering to medicine. A bare FBG is small and light; hence, it can be easily embedded into hosting materials. However, conventional fabrication methods are generally time-consuming with reproducibility issues. A more recent strategy has been proposed to develop novel FBG-based systems by encapsulating the grating within 3-D-printed structures. This process, known as 3-D printing, is characterized by several advantages li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…However, the FE model has not considered the bonding interactions established at the interface between the fiber optic sensor and the 3D-printed material during the printing. Some recent studies showed that an external substrate dampens the strain level experienced by an FBG sensor placed at the specimen core with respect to a nonencapsulated sensor [35], [36]. Hence, we decided to place the optical fiber along the light blue cutline since it can guarantee the optical fiber to be entirely under loading conditions, even if it may experience compression when integrated into the base, as shown in Fig.…”
Section: B Finite Element Analysis and Sensor Positioning Optimizationmentioning
confidence: 99%
“…However, the FE model has not considered the bonding interactions established at the interface between the fiber optic sensor and the 3D-printed material during the printing. Some recent studies showed that an external substrate dampens the strain level experienced by an FBG sensor placed at the specimen core with respect to a nonencapsulated sensor [35], [36]. Hence, we decided to place the optical fiber along the light blue cutline since it can guarantee the optical fiber to be entirely under loading conditions, even if it may experience compression when integrated into the base, as shown in Fig.…”
Section: B Finite Element Analysis and Sensor Positioning Optimizationmentioning
confidence: 99%
“…The most used FOSs applied to tissue palpation are fiber Bragg gratings (FBGs) [19]- [21]. Their use in this scenario can be motivated by the FBGs easy integration into different packaging solutions (e.g., flexible silicones and 3D printing materials) and multiplexing along a single optical fiber to sense exerted forces with high spatial resolution [22]- [26]. FBGs working principle rely on the wavelength demodulation principle, which is not affected by light intensity changes caused by either light power or transmission path [27].…”
Section: Introductionmentioning
confidence: 99%
“…The available literature presents various applications for 3D-printed sensors encapsulating optical fibers. Some notable examples are monitoring of soil deformation [23], [26], [27], structural health [14], [16], [28]- [30], shape sensing [21], [31], pressure evaluation [14], [24], [26], [32]- [36], monitoring of prosthetic limbs [37], [38], and wearables for the measurement of physiological parameters such as joint angles [39], heart rate, and respiratory rate [22]. Due to the wide spectrum of potential applications, the shape and the material of the 3D-printed samples have usually been chosen ad hoc for the specific application.…”
Section: Introductionmentioning
confidence: 99%
“…The shape of the sensor, the material of the filament, the infill geometry, and the infill density are parameters that heavily influence the performance of the sensor. The effect of different infills is analyzed in several studies [22], [27], [35], [36], [40], where the mechanical and thermal properties of the sensor are shown to vary according to infill density and geometry. Embedding the fiber during the 3D printing process is preferable to gluing it in a second moment or on the external surface, since the embedding process ensures a consistent bond between the surfaces and yields a better measurement accuracy [41], [42].…”
Section: Introductionmentioning
confidence: 99%